(NwYWOD OBOB]ENNYH URAWNENIJ KINETIKI FOTONOW I ^ASTIC I IH PRIMENENIE W ASTROFIZIKE (B/s - (NsAPAR(B, (Na(B.-(N|(B. (Na(B.s ((NtALLIN (B:s (NwALGUS(B,s, 1985)
(NbIBLIOGR(B.: (NS(B. 195-198s
(Nan |STssr(B. (NtARTUSKAQ ASTROFIZI^ESKAQ OBSERWATORIQ IM(B. (Nw(B. (NsTRUWEs
Keywords: (NfIZIKAs